Research on the application of information technology of Big Data in Chinese digital library. Issue 8 (11th November 2019) - Li, Shuqing; Hao, Zhiyuan; Ding, Li; Xu, Xia
Abstract : Purpose: Through the case analysis of China's digital library, the purpose of this paper is to make readers understand the development status, achievements and problems of China's digital library. At the same time, it also enables readers to understand the common application forms of these modern information technologies in digital libraries, so as to provide a reference basis for the application of new technologies in other countries' digital libraries. Design/methodology/approach: On the basis of literature review, the authors have analyzed a conspicuous collection of related papers in order to make a comprehensive summary and elaboration on the present situation of modern information technology application in Chinese digital libraries. Findings: This paper defines and analyses the concepts, contents and relationships of the three most important modern Big Data information technologies, and then completes the analysis of the current situation of the application of information technology in Chinese digital libraries. The block chain can achieve more accurate information collection, more secure information storage and more effective information dissemination. Artificial intelligence can improve the existing digital library service level in three aspects: resource construction, information organization and information service. Internet plus will help transform the traditional digital library business mode in order to adapt to the change of user-centered service. Originality/value: This is among the first structured attempts of comprehensively and generally summarizing the application of modern information technology in Chinese digital libraries. It also contains an original exploration of the relationship between the main kinds of modern information technology. Based on this, a relatively complete application scenario and possible vision of modern information technology in digital library can be built.